Ultrafast ion migration in hybrid perovskite polycrystalline thin films under light and suppression in single crystals. Issue 44 (26th October 2016) - Xing, Jie; Wang, Qi; Dong, Qingfeng; Yuan, Yongbo; Fang, Yanjun; Huang, Jinsong
Abstract : This study reveals the important effect of light on ion migration behavior and morphology dependent light stability. Abstract : Understanding the influence of light on ion migration in organic–inorganic halide perovskite (OIHP) materials is important to understand the photostability of perovskite solar cells. We reveal that light could greatly reduce the ion migration energy barrier in both polycrystalline and single crystalline OIHP. The activation energies derived from conductivity measurement under 0.25 Sun decrease to less than one half of the values in the dark. A typical ion drift velocity in CH3 NH3 PbI3 polycrystalline films is 1.2 μm s −1 under 1 Sun, compared with 0.016 μm s −1 under 0.02 Sun. Ion migration across the photoactive layers in most OIHP devices thus takes only subseconds under 1 Sun illumination, which is much shorter than what it was thought to take. Most important of all, ion migration through a single crystal surface is still too slow to be observed even after illumination for two days due to the large ion diffusion activation energy, >0.38 eV.